Multidisciplinary Information Retrieval: 5th International Retrieval Facility Conference, IRFC 2012, Vienna, Austria, July 2-3, 2012 Proceedings - Salampasis, Michail; Larsen, Birger (Lecture notes in computer science, 2012)
This book constitutes the proceedings of the 5th International Information Retrieval Facility Conference, IRFC 2012, held in Vienna, Austria, July 2-3, 2012. The 12 papers presented were carefully reviewed and selected from 17 high-quality submissions. IRF conferences wish to bring young researchers into contact with industry at an early stage. This fifth conference aimed to tackle four complementary research areas: information retrieval, machine translations for search solutions, and interactive information access. The papers are organized into topical sections on patent search, Web search, applications, and query formulation and analysis.
Keywords: Konferenzschrift -- 2012 -- Wien; Wissensverarbeitung; Sprachverarbeitung; Semantic Web; Information Retrieval